The Wayqecha Amazon Cloud Curtain Ecosystem Experiment: A new experimental method to manipulate fog water inputs in terrestrial systems - Daniel B. Metcalfe; Darcy F. Galiano Cabrera; Luis Miguel Alvarez Mayorga; Roxana Sacatuma Cruz; Daniela Corrales Alvarez; Blanca Rosa Espinoza Otazu; Walter Huaraca Huasco; Jimmy R. Chambi; Maria E. Ezquerra; Beisit L. Puma Vilca; Mark Mulligan; Matthew A. Vadeboncoeur; et al. (Methods in Ecology and Evolution)
Abstract Fog makes a significant contribution to the hydrology of a wide range of important terrestrial ecosystems. The amount and frequency of fog immersion are affected by rapid ongoing anthropogenic changes but the impacts of these changes remain relatively poorly understood compared with changes in rainfall. Here, we present the design and performance of a novel experiment to actively manipulate low lying fog abundance in an old‐growth tropical montane cloud forest (TMCF) in Peru—the Wayqecha Amazon Cloud Curtain Ecosystem Experiment (WACCEE). The treatment consists of a 30 m high, 40 m wide mesh curtain suspended between two towers and extending down to the ground, and two supplementary curtains orientated diagonally inwards from the top of each tower and secured to the ground upslope. The curtains divert and intercept airborne water droplets in fog moving upslope, thereby depriving a ~420 m2 patch of forest immediately behind the curtains of this water source. We monitored inside the treatment and a nearby unmodified control plot various metrics of water availability (air humidity, vapour pressure deficit, leaf wetness and soil moisture) and other potentially confounding variables (radiation, air and soil temperature) above and below the forest canopy. The treatment caused a strong reduction in both air humidity and leaf wetness, and an increase in vapour pressure deficit, above the canopy compared to the control plot. This effect was most pronounced during the nighttime (20:00–05:00). Below‐canopy shifts within the treatment were more subtle: relative humidity at 2 m height above the ground was significantly suppressed during the daytime, while soil moisture was apparently elevated. The treatment caused a small but significant increase in air temperature above the canopy but a decrease in temperature in and near the soil, while mixed effects were observed at 2 m height above the ground. Above‐canopy radiation was slightly elevated on the treatment relative to the control, particularly during the dry season. Further application of the method in other systems where fog plays a major role in ecosystem processes could improve our understanding of the ecological impacts of this important but understudied climate driver.